2011
DOI: 10.1038/onc.2011.140
|View full text |Cite
|
Sign up to set email alerts
|

Control of tumor and microenvironment cross-talk by miR-15a and miR-16 in prostate cancer

Abstract: The interaction between cancer cells and microenvironment has a critical role in tumor development and progression. Although microRNAs regulate all the major biological mechanisms, their influence on tumor microenvironment is largely unexplored. Here, we investigate the role of microRNAs in the tumor-supportive capacity of stromal cells. We demonstrated that miR-15 and miR-16 are downregulated in fibroblasts surrounding the prostate tumors of the majority of 23 patients analyzed. Such downregulation of miR-15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
163
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(174 citation statements)
references
References 50 publications
7
163
0
2
Order By: Relevance
“…These data may help to develop new therapeutic strategies to target the prostate tumor stroma under androgen-manipulated conditions. Interestingly, a recent study has demonstrated that downregulation of the micro-RNAs miR-15 and miR-16 in prostate cancer-associated fibroblasts (CAFs) promotes tumor growth and progression through the reduced post-transcriptional repression of FGF2 and of its receptor FGFR1 [90]. Moreover, reconstitution of miR-15 and miR-16 significantly impaired the tumor-supportive capability of stromal cells in vitro and in vivo, thus enforcing the therapeutic concept aimed at reconstituting the expression of these micro-RNAs in advanced prostate cancer [90].…”
Section: The Role Of the Fgf/fgfr System In Tumor/stroma Cross-talkmentioning
confidence: 99%
“…These data may help to develop new therapeutic strategies to target the prostate tumor stroma under androgen-manipulated conditions. Interestingly, a recent study has demonstrated that downregulation of the micro-RNAs miR-15 and miR-16 in prostate cancer-associated fibroblasts (CAFs) promotes tumor growth and progression through the reduced post-transcriptional repression of FGF2 and of its receptor FGFR1 [90]. Moreover, reconstitution of miR-15 and miR-16 significantly impaired the tumor-supportive capability of stromal cells in vitro and in vivo, thus enforcing the therapeutic concept aimed at reconstituting the expression of these micro-RNAs in advanced prostate cancer [90].…”
Section: The Role Of the Fgf/fgfr System In Tumor/stroma Cross-talkmentioning
confidence: 99%
“…There are some miRNAs that have been found to influence tumor microenvironment. 24 This extensive body of knowledge points to miRNAs as potentially being novel cancer biomarkers, and as such they have several advantageous features. The small size and distinctive biochemical structure of miRNAs makes them resistant to endogenous RNase activity.…”
Section: Mirnas As Biomarkers In Prostate Cancer Pathogenesismentioning
confidence: 99%
“…Lately miRNA has also become implicated in signaling between stromal and epithelial cells and some recent reports [28,29] have provided evidence suggesting that traffic of miRNA subtypes between disseminated cancer cells and bone marrow stromal cells can influence whether the cancer cells establish metastatic colonies or remain in dormant state. If these findings are corroborated, it will show that non-proteinaceous molecules also convey signals between interacting cell populations in the tumor microenvironment, which can determine whether tumor cells can fulfill an already activated, intrinsic potential towards malignant behavior.…”
Section: Ii) Cancer Formation: Microscopic and Cellular Aspectsmentioning
confidence: 99%